Narratives of Obeah in West Indian literature: moving through the margins - Rodriques, Janelle (Routledge, 2019)
Cover; Half Title; Title Page; Copyright Page; Dedication; Contents; Acknowledgements; Introduction: Obeah as cultural signifier; 1 'Too much row an' contention is in this yard:' contemplating cacophony in Minty Alley and Black Fauns; 2 'Part of the narrative of modern art yet not central enough to be considered constitutive:' 'Primitive Modern' in Banana Bottom and Wide Sargasso Sea; 3 'It is the reader who constructs a story:' Obeah and cultural identity in the mid-century West Indian short story; 4 Obeahmen as heroes, in 'a zone of direct contact with developing reality'